Peran Usaha Industri Kecil Pangan Terhadap Pengembangan Wilayah di Kecamatan Tuah Madani Kota Pekanbaru - Yasser Hamidi; Trisla Warningsih; Dahlan Tampubolon (SYNERGY: Jurnal Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of production factors (working capital, labor, raw materials, and technology) on the production output of small food industries and to analyze the role of small food industries in regional development in Tuah Madani District, Pekanbaru City. The research method used a quantitative approach with Cobb-Douglas multiple regression analysis to answer the first objective, while the second objective was analyzed using the Location Quotient (LQ) and multiplier effect methods. The research population consisted of 138 small food industry units in Tuah Madani District. A sample of 58 businesses was selected using the Slovin formula with a significance level of 10% and purposive sampling technique. The results showed that the four production factors simultaneously had a significant effect on production output with an F-value of 386.502 and a significance level of 0.000. The regression model formed had excellent predictive power with an R² value of 96.7%, meaning that 96.7% of the variation in production output could be explained by the variables of working capital, labor, raw materials, and technology. Partially, raw materials have the most significant influence with a coefficient of 0.635 and a t-value of 7.515, followed by technology with a coefficient of 0.139 and a t-value of 3.841. The Location Quotient analysis shows a value of 2.54, indicating that the small food industry is a base sector in Tuah Madani District. The multiplier effect analysis produced a value of 4 for the income multiplier and employment multiplier, indicating a significant multiplier effect on the regional economy. Small-scale food industries have proven to play an important role in regional development through the absorption of local labor (70.7% of whom are women), increased community income, and the creation of an economic multiplier effect that influences other economic sectors